Determinants of left ventricular mass in obesity; a cardiovascular magnetic resonance study. - Rider, O; Francis, J; Ali, M; Byrne, J; Clarke, K; Neubauer, S; Petersen, SE (2009)
BACKGROUND: Obesity is linked to increased left ventricular mass, an independent predictor of mortality. As a result of this, understanding the determinants of left ventricular mass in the setting of obesity has both therapeutic and prognostic implications. Using cardiovascular magnetic resonance our goal was to elucidate the main predictors of left ventricular mass in severely obese subjects free of additional cardiovascular risk factors. METHODS: 38 obese (BMI 37.8 +/- 6.9 kg/m2) and 16 normal weight controls subjects, (BMI 21.7 +/- 1.8 kg/m2), all without cardiovascular risk factors, underwent cardiovascular magnetic resonance imaging to assess left ventricular mass, left ventricular volumes and visceral fat mass. Left ventricular mass was then compared to serum and anthropometric markers of obesity linked to left ventricular mass, i.e. height, age, blood pressure, total fat mass, visceral fat mass, lean mass, serum leptin and fasting insulin level. RESULTS: As expected, obesity was associated with significantly increased left ventricular mass (126 +/- 27 vs 90 +/- 20 g; p < 0.001). Stepwise multiple regression analysis showed that over 75% of the cross sectional variation in left ventricular mass can be explained by lean body mass (beta = 0.51, p < 0.001), LV stroke volume (beta = 0.31 p = 0.001) and abdominal visceral fat mass (beta = 0.20, p = 0.02), all of which showed highly significant independent associations with left ventricular mass (overall R2 = 0.77). CONCLUSION: The left ventricular hypertrophic response to obesity in the absence of additional cardiovascular risk factors is mainly attributable to increases in lean body mass, LV stroke volume and visceral fat mass. In view of the well documented link between obesity, left ventricular hypertrophy and mortality, these findings have potentially important prognostic and therapeutic implications for primary and secondary prevention.